PENGARUH LEVERAGE, PREDIKTABILITAS LABA, SIZE TERHADAP EARNING RESPON COEFFICIENT (ERC) PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Rasma Kiranasari, 09.05.52.0186; Setyowati, Widhy (Students Journal of Accounting and Banking, 2013)
The purpose of this study is to examine and analyze the effect of firm size (size), capital structure (leverage) and, predictability of earnings on Earnings Response Coefficient (ERC) on the property and real estate companies listed on the Indonesia Stock Exchange in 2008-2011.The study population is the property and real estate company that has been registered and issued financial statements in Indonesian Stock Exchange (BEI) of the year 2008-2011. Samples were taken by using purposive sampling method, ie the population to be sampled is a study that meets certain criteria sample according to the desired research and then selected based on certain considerations penelitian.Metode adapted to the purpose that is in use is the multiple regression analysis mode.The results showed capital structure (leverage) does not significantly influence the response koefisin earnings in property and real estate companies in Indonesia Stock Exchange in the period 2008-2011. Earnings predictability significant effect on earnings response koefisin on property and real estate companies in Indonesia Stock Exchange in the period 2008-2011. Variable firm size (size) does not significantly influence the response koefisin earnings in property and real estate companies in Indonesia Stock Exchange in the period 2008-2011.Keywords: Product quality, Brand Image, Price Perseptions, Promotion and Purchase Decisions